Gestión operativa y su incidencia en la rentabilidad de la hacienda agrícola "Laurita" del cantón La Maná, provincia de Cotopaxi año 2014, modelo de gestión operativa. - Cañas Trejo, Shirley María (2015)
This thesis, operational management and its impact on the profitability of the Agricultural Finance "LAURITA" Canton La Mana, 2014, the following objectives: to investigate the operational management strategies employed by the company for decision-making, determining financial performance according to the financial statements, establish operational management indicators based on business needs and design a model that would strengthen operational management procedures of the production area of the Treasury. In this thesis concepts, theories and laws of other authors provided them with their studies, so that books, theses, academic articles and websites were used were taken. Types, methods, designs and research instruments, which allowed achieve the objectives, population and sample were formed by the manager and employees of the company which was applied interview forms and surveys were also used. This research presented a proposed alternative to the design of an operational management model that allows consistently allocate resources Agricultural Finance "LAURITA", 2015. This design will help maintain an efficient organizational structure for achieving objectives through compliance procedures, regulations and internal policies. The results showed that the company uses as operational management strategies; well defined organizational structure, values, work performance evaluations, rules, manual functions, but needs to improve the system of internal control. As for the economic performance of the company, they have been favorable for growth, since in 2013 the Treasury generated 885,500 boxes of bananas in 385 hectares and in 2014 came to 907,637.50 boxes. Operational management indicators showed that the operational management needs to improve its efficiency by 31.83%, the effectiveness of time established for the development of the activities to be performed in 36.36%, while the level of economy must be improved by 40.91%.